Myelonecrosis: A Clinicopathological Study from a Tertiary Care Center in South India over a Twelve-Year Period. (23rd January 2014) - Rekha, Jinkala Sree; Kar, Rakhee; Basu, Debdatta
Abstract : Aims . To study the etiology, diagnostic features, and clinical significance of myelonecrosis. Methods . A retrospective review of all trephine biopsies done over 12 years (January 2000 to December 2012) in Department of pathology was done and all trephine biopsies showing MN were identified and studied. Results . Twenty-five cases accounting for 0.4% were identified. Fever and generalized weakness were the common presenting symptoms. Anemia was seen in all cases followed by thrombocytopaenia. Malignancy was the underlying cause in 64% of cases; hematolymphoid malignancy was seen in two-thirds and solid malignancies in one-third of the cases. Tuberculosis accounted for 16% of the cases and the etiology was unknown in 12%. Conclusions . The causes of MN are varied and hematological malignancy and solid malignancies are the most common causes. Presence of myelonecrosis is associated with a poor prognosis. Myelonecrosis may obscure the underlying disorder and hence a thorough search in the bone marrow biopsy itself with the help of immunohistochemistry may prove worthwhile in identifying the underlying disease.